PELATIHAN DAN PRAKTIK PEMBUATAN MOKANUSA COOKIES CHEWY BERBASIS MOCAF DESA MERAK BATIN, KECAMATAN NATAR, KABUPATEN LAMPUNG SELATAN - sutarto, sutarto; Dewi Puspita Sari, Ratna; Lusi Nugraheni, Irma; Anggileo Pramesona, Bayu; Komala, Ramadhana; Eka Yunianto, Andi; Saragih, Rebecca A F; Musadad, Niam; Kahar, Farid; Kesuma, Wijaya; Fajar Indriansyah Valian, Ihsan; Zaskia Suryadi, Najwa; Kevina; Dima Fasya, Arina; Arbi, M Anugrah; Raditia Maulana, Faras; Adela, Tamara; Kurniawati, Murni; Zahra, Alvika (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2026)
This community service program aimed to improve community knowledge and skills in utilizing mocaf flour as an alternative to wheat flour through training on producing MokaNusa Chewy Cookies in Merak Batin Village, South Lampung. The method applied a participatory approach involving education, hands-on practice, and continuous assistance. A total of 27 participants were involved, mostly aged over 40 years. The evaluation results showed an increase in average knowledge scores from 68.15 to 84.81, with an improvement of 16.66 points, and 70.4% of participants experienced increased knowledge. Participants were also able to independently apply the processing skills. This program proved effective in enhancing community capacity, promoting local food diversification, and creating opportunities for home-based businesses to support food security and economic empowerment.